SOCIAL DISTANCES AS A FEATURE OF THE CONTEMPORARY RUSSIAN SOCIAL SPACE - Belyaeva, L.A. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2018)
Social space is a theoretical construct that allows to consider many key problems of social development including the society’s consolidation. The author defines social space as a set of social statuses and distances. Their objective characteristics are interrelated with subjective indicators identified through the opinions of individuals. The balance of statuses and distances in society and the acceptability of this structure for the majority of population ensure the stability of society and effective social control. If this balance is disturbed, social tensions arise and threaten the stability and consolidation of society. Thus, the ideas of the theories of social space possess a considerable heuristic potential for revealing urgent problems of social development such as solidarity, social stratification and mobility, social networks and their interaction, connections of local communities within and with the world, interaction of structured social relations and individual and collective practices, genesis of social space as a result of social production represented by both things and relationships, etc. According to the theory of P. Bourdieu, the author con-siders social space as a structure of social statuses based on the set of different types of capital: economic, cultural, social, and symbolic. The author uses statistical data and results of the monitoring survey conducted on the all-Russian sample. The article proposes some tested empirical indicators that proved the increase of social distances in Russia due to the redistribution of economic capital and, as a consequence, of cultural and social capitals. Thus, the social space of Russia cannot be considered stable. To ensure its greater stability we need a set of measures to reduce social distances: re-industrialization to create high-tech jobs, development of digital economy, and improvement of the mass secondary and higher education system - these measures can create a basis for the upward social mobility.